Development and Evaluation of an Interactive E-Module for Virtualization and Cloud Technology Learning in Computer Engineering Education - Rhesky Annisa Basri; Jumadi Mabe Parenreng; Mustari S. Lamada (PT. Global Research Collaboration, 2026)
Background/Context: The transformation of learning in higher education requires the availability of structured and interactive digital teaching materials that support independent and practice-based learning. In the Virtualisation and Cloud Technology course, the limited availability of standardised learning modules has resulted in suboptimal learning processes and inconsistencies in students’ learning outcomes. Objective/Purpose: his study aimed to develop an electronic module (e-module) for the Virtualisation and Cloud Technology course in the Computer Engineering Study Programme at Makassar State University to enhance learning effectiveness, conceptual understanding, and students practical skills. Method: This study employed a research and development approach using the 4D model, which consists of the define, design, develop, and disseminate stages. The e-module was validated by subject matter experts and media experts, followed by small-group and large-group trials. Its effectiveness was evaluated through pre-test and post-test assessments. Results: The validation results indicated that the e-module demonstrated very high quality in terms of content and media design. Student responses showed that the e-module was practical to use and supported the learning process. Furthermore, the implementation of the e-module significantly improved students’ learning outcomes and promoted independent learning as well as deeper conceptual understanding. Conclusion: The developed Virtualisation and Cloud Technology e-module was found to be valid, practical, and effective as a digital learning resource. Its use contributes positively to improving learning outcomes and the overall quality of instruction, making it suitable for implementation in higher education, particularly in technology- and practice-oriented courses.